Understanding Green Creative Behavior Driven by Parenting and Entrepreneurial Orientation on Entrepreneurship Students in Indonesia and Malaysia - Prabandari, Sri Palupi; Puspaningrum, Astrid; Yulianti, Ida; Rasli, Amran Bin Md; Kurniasari, Irma (International Review of Management and Marketing, 2026)
The objective of this study is to explain the influence of parenting and entrepreneurial orientation on green creative behavior (GCB) among entrepreneurship students in Indonesia and Malaysia, with a focus on sustainable innovation and family support in promoting environmentally friendly business models. This research employed a quantitative approach with surveys as the data collection method. Data were gathered from 124 respondents using questionnaires distributed through Google Forms, targeting students who own environmentally friendly businesses. The analysis was conducted using SmartPLS to examine the relationships between variables through the Structural Equation Modeling (SEM) approach. The study's results indicate that parenting has a significant and positive impact on green creative behavior, and entrepreneurial orientation acts as a mediator in this relationship. Parenting not only influences values and attitudes toward environmental sustainability but also supports the development of higher entrepreneurial orientation among students. However, this study had several limitations, such as restricted geographic and demographic scope, making the results not globally generalizable. Future research is recommended to expand the research scope and employ a combination of quantitative and qualitative methods to gain more comprehensive insights.